BASIC PROVISIONS OF INTERCORPORATE RELATIONS MANAGEMENT IN INTEGRATION OF ECONOMIC ENTITIES - KARPENKO, VITALII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The existing approaches to management and administrative interaction in corporations and intercorporate relations are generalized, which allowed to distinguish the following principles of integration of economic entities: voluntary association, trust, equality, mutual benefit, consolidation of common interests, justice and democracy, contractual nature of relations coordination of economic activity, mutual exchange of knowledge, achievements and information, motivation to achieve strategic goals, joint strategy development, competitive advantages, marketing focus, economic efficiency.It is determined that the development of stable inter-corporate relations shows that their participants receive certain benefits. These advantages are obvious: they allow to increase their adaptability and speed of reaction to changes in market conditions; significantly reduce costs and determine their rational structure; provide an opportunity to involve optimal partners in joint activities, eliminate cooperation with unreliable counterparties. These benefits, in our opinion, determine the main reasons for the emergence of intercorporate relations in the integration of economic entities: the overall goals of product creation (value) and the ability to save costs. The first reason allows economic agents to achieve their integration goals by focusing on collaborative development or the use of different types of resources, such as knowledge, technology, information, human resources, infrastructure, and so on. The second reason for the development of inter-corporate relations in the integration of economic entities is the ability to optimize transaction costs compared to costs incurred without stable partnerships. Such transaction costs should include the costs of negotiating and concluding contracts, finding information about partners and markets, logistics costs, and so on.
Keywords: management; integration; partnership; relations; intercorporate relations; co-opetition; synergy effect